Ensino e aprendizagem em Matemática na educação de pessoas jovens, adultas e idosas - EPJAI: um estudo em uma escola do campo em Paripiranga-BA - Santos, Josefa Manuela dos (2024)
The invisibility associated with certain social groups is a significant factor contributing to unrest and the quest for change, particularly within educational and sociocultural contexts. Thus, essential reflections and attitudes concerning Rural Education and Education for Young, Adults, and Elderly People (EYAEP) emerge, recognizing that these modalities originate from a context of struggle and resistance, against historical contexts marked by exclusion and decontextualized education aimed only at specific groups or types of work. From this perspective, the study in question was developed, based on the research problem: “What are the perceptions and practices of teaching and learning in mathematics presented by EYAEP professionals and students in a Rural School in Paripiranga-BA?” The general objective is to analyze the perceptions and practices of teaching and learning Mathematics at EYAEP in a Rural School in Paripiranga-BA. To achieve this, the following specific objectives were defined: a) to list the perceptions of teachers and students participating in the research regarding EYAEP and Rural Education and the specificities of teaching and learning mathematics in this context; b) to relate the mathematics teaching practices developed within the research context; c) to identify possible relationships between the political-pedagogical principles of EYAEP and Rural Education in teaching and learning mathematics at the research site. This study is an exploratory case study, descriptive and explanatory in nature. The methodological procedures include the analysis of bibliographic data through meta-analysis of productions from the Brazilian Digital Library of Theses and Dissertations (BDLTD) on the object of study, and the conducting of semi-structured interviews with research participants. Participants in the study include project coordination members, three teachers (one from each teaching area), one pedagogue and one agronomist, 18 students from Phase I (initial years of elementary school) and Phase II (final years of elementary school), and three community members involved with the project. Among the main theoretical references are Freire (1979, 1994, 2017), Caldart (2004, 2010), D’Ambrosio (1991, 1997, 1998, 2009, 2018), Arroyo (2011, 2017), and Haddad and Di Pierro (2000). The primary results highlight the need for further studies involving Rural Education and the integrated Education of Young, Adult, and Elderly People. Additionally, regarding the EYAEP Rural project in the Baixão community, located in Paripiranga-BA, it is identified that this project is based on principles of contextualized, liberating, and transformative education, aligning with the principles of Alternation Pedagogy and Ethnomathematics. A diagnosis of the historical, social, and cultural context of the community is conducted, identifying the problems and potentialities for developing methodologies and strategies that mitigate/solve the identified issues and expand the potentialities, articulating practices through the constructed experiment at school, the agroecological mandala, Community Times/School Times, and Knowledge Sharing.